Smoker's melanosis or early melanoma- misdiagnosis trap? - S.O. Nwhator (Nigerian Dental Association, 2020)
Objective: First used by Hedin in 1977, "smokers' melanosis" is currently recognized as a clinical diagnosis without recourse to biopsy. Current research findings however suggest the disturbing possibility of mistaking a "silent" oral malignant melanoma for a benign smokers' melanosis. The objective of the current review is to stimulate an evidence-based rethink. Method: This manuscript is based on a Pubmed search phrase "smokers' melanosis". Result: A total of 24 studies resulted of which 16 were analyzed and 8 non-oral melanomas were excluded. Reports ranged from claims of a  "protective" role of melanosis to cases of melanoma from pre-existing melanosis. Alcohol synergistic potentiation of intra-oral melanosis and a categorization of smokers' melanoma as a differential for intra-oral smokers' melanosis were also found. Conclusion: Since many cases of confirmed intra-oral malignant melanomas were preceded with a history of pre-existing "innocent" oral pigmented lesions, adopting a principle of universal biopsy is strongly suggested. This would change this age-long paradigm but would definitely save a few lives.